Production and characterization of bacterial cellulose scaffold and its modification with hyaluronic acid and gelatin for glioblastoma cell culture - YILMAZ, BETÜL; OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN; ÜNAL YILDIRIM, SEMRA (SPRINGER, 2021)
Three-dimensional (3D) in vitro cell culture models have recently gained increasing interest in predicting the response of anticancer drugs. In this study first, we tried to obtain a novel hyaluronic acid (HA)/gelatin (Gel) modified bacterial cellulose (BC) composite scaffolds by in situ fermentation method. Morphological and chemical structures, wettability, and thermal stability of scaffolds were evaluated. In particular, the human glioblastoma (GBM) cancer cell line (U251) was seeded into BC/HA/Gel scaffolds to evaluate their potential as in vitro 3D cancer cell culture. MTT proliferation assay, scanning electron microscopy, and confocal microscopy were utilised to determine cell proliferation, morphology and adhesion. The results suggest that our hyaluronic acid and gelatin modified bacterial cellulose scaffold is promising to be used as in vitro 3D culture of GBM cells and may be used to predict treatment response or reactions of new therapeutics.
Keywords: Bacterial cellulose; Hyaluronic acid; Gelatin; Glioblastoma; 3D culture; GRAPHENE OXIDE; 3D; GLIOMA; NANOFIBERS; MIGRATION; PROLIFERATION; FABRICATION; RESISTANCE; MEMBRANES; BEHAVIOR